From apoplexy in antiquities to cerebrovascular stroke in modernity: a narrative timeline and tale - Tamer Roushdy (The Egyptian Journal of Neurology, Psychiatry and Neurosurgery)
Abstract Background Stroke is one of the commonest encountered brain and neurological disorders worldwide. Stroke management has had a major shift in the last 50 years and precisely since the discovery and approval of thrombolysis as an acute management followed by multiple trials on mechanical thrombectomy and its approval. Yet, Stroke is as old as the history of mankind. Historically stroke symptoms’ description is older than the descriptions of the Greco-Roman civilization (500 BC – 800 AD). Before Stroke, the term apoplexy was described in ancient civilizations and evidence of suffering and managing it is preserved within the mummies, inscriptions, and papyri of the Egyptian civilization, clay tablets of the Mesopotamian civilization, medical books of the Chinese civilization, and although physicians and scientists consider the Greco-Roman civilization the base for modern medicine, yet the golden age of Islam (800 – 1200 AD) might have shared more in identifying bases of stroke. The European Renaissance beginning from 1400 AD with its famous anatomists and physicians greatly contributed too to stroke localization and vascular supply. Conclusions As medicine and science are in a continuous chain from the past to the future through the present, the current comprehensive review highlights the major important and documented shifts in the history of stroke over more than 4500 years starting from ancient civilizations BC up to 2024 AD.